Sleep and dreaming are for important matters - Perogamvros, Lampros; Dang-Vu, Thien Thanh; Desseilles, Martin; Schwartz, Sophie (Frontiers in Psychology, 2013)
Recent studies in sleep and dreaming have described an activation of emotional and reward systems, as well as the processing of internal information during these states. Specifically, increased activity in the amygdala and across mesolimbic dopaminergic regions during REM sleep is likely to promote the consolidation of memory traces with high emotional/motivational value. Moreover, coordinated hippocampal-striatal replay during NREM sleep may contribute to the selective strengthening of memories for important events. In this review, we suggest that, via the activation of emotional/motivational circuits, sleep and dreaming may offer a neurobehavioral substrate for the offline reprocessing of emotions, associative learning, and exploratory behaviors, resulting in improved memory organization, waking emotion regulation, social skills, and creativity. Dysregulation of such motivational/emotional processes due to sleep disturbances (e.g., insomnia, sleep deprivation) would predispose to reward-related disorders, such as mood disorders, increased risk-taking and compulsive behaviors, and may have major health implications, especially in vulnerable populations.